Interaction of laser radiation with matter. Laser plasma : Peculiarities of the formation of photonic nanojets by a matrix of dielectric microtoroids. (31st August 2020) - Geints, Yu E; Panina, E K; Zemlyanov, A A
Abstract: We report the results of theoretical modelling of photonic nanojets (PNJs) formed by laser radiation scattering on a single-layer ordered assembly of dielectric microtoroids placed on the surface of a transparent matrix (silicone film). Using the method of computational electrodynamics (FDTD), the main PNJ parameters (length, width, peak intensity) are analysed under the conditions of mutual influence of the light fields of neighbouring microparticles. It is shown that the main factor affecting the PNJ characteristics under study is the spatial configuration of the radiation-scattering particle, namely, the internal diameter of its cross section. It is found that for certain configurations of toroid placement in a cluster, a PNJ ensemble is implemented with parameters significantly better than those for a single toroid.